2006
DOI: 10.5507/bp.2006.043
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Brain Natriuretic Peptides Investigation in Various Cardiovascular Diseases

Abstract: Background: Brain natriuretic peptides are relevant markers of heart impairment. Aim: We investigated the relevance of investiging brain natriuretic peptides (NT-proBNP, BNP) in monitoring different types of cardiovascular disease (chronic heart failure due to coronary artery disease, cardiomyopathy, acquired valve disease, congenital heart diseases).Methods: The NT-proBNP assay (Roche) was performed on 280 patients (mean age 49 years; range 20-89 years) and 48 healthy controls (mean age 43 years; range 13-65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…The present results confirm the findings of other studies showing significantly elevated levels of natriuretic peptides in various types of congenital and valvular heart diseases [3][4][5] . Other studies have shown a relationship between concentrations of natriuretic peptides and severity of heart failure [6][7][8][9][10][11][12] . In agreement with previous publications [6][7][8][9][10][11][12] , the levels of both natriuretic peptides increased with severity of the heart impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results confirm the findings of other studies showing significantly elevated levels of natriuretic peptides in various types of congenital and valvular heart diseases [3][4][5] . Other studies have shown a relationship between concentrations of natriuretic peptides and severity of heart failure [6][7][8][9][10][11][12] . In agreement with previous publications [6][7][8][9][10][11][12] , the levels of both natriuretic peptides increased with severity of the heart impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown a relationship between concentrations of natriuretic peptides and severity of heart failure [6][7][8][9][10][11][12] . In agreement with previous publications [6][7][8][9][10][11][12] , the levels of both natriuretic peptides increased with severity of the heart impairment. The highly significant relationship to age and gender for both natriuretic peptides found, accords with other studies [13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Natriuretic peptides are widely used for the diagnosis of heart failure, for monitoring the efficacy of the treatment, or as a prognostic marker in the general population with cardiovascular diseases as well as in adults with congenital heart disease [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Steigende Werte stehen in Wechselbeziehung mit der Mortalität und Morbidität; es ist demzufolge als Marker von prognostischer Bedeutung (Anand et al 2003). In zahlreichen Studien wurde der Nutzen der BNP-Bestimmung bei kardiovaskulären Erkrankungen nachgewiesen (hier beispielsweise Kotaska et al 2006). Man kann BNP als einen quantitativen Marker ansehen; umso höher das BNP, desto höher ist die Wahrscheinlichkeit, dass eine Herzinsuffizienz vorliegt (Mueller et al 2007).…”
Section: Bnpunclassified